Lipid damage is the best marker of oxidative injury during the cardiac remodeling process induced by tobacco smoke - Lourenço, Maria Angélica Martins [UNESP]; Braz, Mariana Gobbo [UNESP]; Aun, Aline Garcia [UNESP]; Pereira, Bruna Letícia Buzati [UNESP]; Fernandes, Fábio Henrique [UNESP]; Kazmarek, Elisa Moya [UNESP]; Bachiega, Tatiana Fernanda [UNESP]; Zanati, Silmeia Garcia [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; et al. (Springer Nature, 2018)
BACKGROUND: Oxidative stress is one potential mechanism that explain the direct effects of smoking on cardiac remodeling process. However, no study has compared different myocardial products of macromolecule oxidation after tobacco smoke exposure. Thus, the aim of this study was to investigate the lipid hydroperoxide (LH) levels, protein carbonyl concentrations and DNA damage in cardiac tissue of rats exposed to tobacco smoke. METHODS: Male Wistar rats were divided into two groups: group C (control, n = 14) composed of animals not exposed to cigarette smoke; group ETS (exposed to tobacco smoke, n = 14) composed by animals exposed to cigarette smoke. The animals were exposed to 2 month of ETS and morphological, biochemical and functional analyses were performed. RESULTS: Cardiac cotinine levels were elevated in the ETS group. In addition, the myocyte cross-sectional area was higher in the ETS group. (C = 266.6 ± 23.2 μm2 and ETS = 347.5 ± 15.1 μm2, p <  0.001). Cardiac LH was higher in the ETS group than in group C (C = 196.4 ± 51.5 nmol/g and ETS = 331.9 ± 52.9 nmol/g, p <  0.001). However, there were no between-group differences in cardiac protein carbonyl concentration or DNA damage. CONCLUSIONS: Therefore, our results suggest that, in this model, lipid damage is a good marker of oxidative damage during the cardiac remodeling process induced by 2 months of exposure to tobacco smoke.
Keywords: Cigarette smoke; Comet assay; DNA damage; Protein carbonyl groups